Западный зной: роман / Чингиз Абдуллаев - Абдуллаев Чингиз Акифович (Эксмо, 2007)
Экземпляры: (2012) / Инвентарный номер: 47663 / Цена: 115.00 / Сис.шифр: Р2 / Авт.знак: А 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6